Small molecule probes for the specific imaging of monoamine oxidase A and monoamine oxidase B - Yi Fang; Zhengping Chen; Min Yang (iRADIOLOGY, 2024)
Abstract Monoamine oxidases (MAOs) are a class of flavin enzymes that are mainly present in the outer membrane of mitochondria and play a crucial role in maintaining the homeostasis of monoamine neurotransmitters in the central nervous system. Furthermore, expression of MAOs is associated with the functions of peripheral organs. Dysfunction of MAOs is relevant in a variety of diseases such as neurodegenerative diseases, heart failure, metabolic disorders, and cancers. Monoamine oxidases have two isoenzymes, namely, monoamine oxidase A (MAO‐A) and monoamine oxidase B (MAO‐B). Therefore, the development of reliable and specific methods to detect these two isoenzymes is of great significance for the in‐depth understanding of their functions in biological systems, and for further promoting the clinical diagnosis and treatment of MAO‐related diseases. This review mainly focuses on the advances in small molecular probes for the specific imaging of MAO‐A and MAO‐B, including radiolabeled probes, fluorescent probes, and a 19F magnetic resonance imaging probe. In addition, applications of these probes for detecting MAO expression levels in cells, tissues, animal models, and patients are described. Finally, the challenges and perspectives of developing novel MAO imaging probes are also highlighted.